Penyisihan Konsentrasi Pb Menggunakan Typha Latifolia Dengan Metode Sub- Surface Flow Constructed Wetland - Sanny Amir Arasy; Shinta Elystia; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Lead (Pb) is a heavy metal that has a high toxicity and the presence in water or wastewater could be derived from industrial activities, agriculture and mining. Oneof technology could be applied to eliminate Pb in wastewater is constructed wetland using Typha latifolia. This research aims to study the ability of Typha latifolia to reducing Pb on variations are concentration of artificial wastewater by 10; 30 and60 mg/L and detention time 1; 2; 3; 4 and 5 days. Concentration of Pb in wastewater was analyzed using atomic absorption spectrophotometer (AAS). The results showedremoval efficiency of Pb increases with longer detention time. The highest removal of Pb occurs at a concentration of 10 mg/L; 5 days detention time amounted to 87,40%and at the final of the experiment concentration of Pb to 1,26 mg/L. While the lowest efficiency at 5 days detention time occurs at concentrations of Pb 60 mg/L with a removal efficiency of 54,46 %, with a final concentration of 27,32 mg/L.Keywords: constructed wetland, detention time, Pb, Typha latifolia